(untitled) (African Journal of Biomedical Research, 2023)
This study was aimed at identifying and documenting medicinal plants used as medicines in the traditional treatment of infections of the digestive tract (diarrhea, oral thrush and anites) by traditional healers in the central region of Togo. The data were collected by semi-structured interviews method from 45 traditional practitioners. This study identified 61 plants species, from 54 genera and 26 botanical families. The most represented families were Fabaceae (9 genera / 9 species), Asteraceae (5/5), Combretaceae (4/5), Moraceae (2/5) and Euphorbiaceae (4/4). The most cited species are: Parkia biglobosa (Frequency of Citation = Frequency of citation = 12.92%), Pteleopsis suberosa (Frequency of Citation = 8.31%), Maytenus senegalensis (Frequency of Citation = 8.31%), Anchomanes difformis (Frequency of Citation = 7.38%) and Hymenocardia acida (Frequency of Citation = 4.37%). Sixty-seven percent (67%) of the identified plants are used in the treatment of childhood diarrhea. The leaves (30%) are the most used plant parts followed by stem barks. The decoction (59%) is the most used mode of preparation. The oral route (66%) remains the main route of administration of the phytomedicines. The medicinal plants are important in the traditional treatment of childhood infections in the central region of Togo. It is therefore necessary to investigate the effectiveness and toxicity of these plants for a better traditional use.